Social partnerships among academia, industry, and government in education: a bibliometric analysis - Sadykova, Aigul; Berikkhanova, Aiman; Atabekova, Baktygul; Sholpankulova, Gulnar; Abdykhalykova, Zhazira (Frontiers in Education, 2025)
This paper employed a bibliometric analysis technique to explore the literature on social partnership in education, aiming to uncover historical trends, research focus areas, influential publications, and contributors. Adopting a retrospective observational design, this study examined 1,208 journal articles in the Lens database from 1983 to 2023 related to education-practice partnerships. The research on the topic showed limited activity until late years, with a surge in publications. Key areas of interest included government involvement, healthcare-related partnerships, and collaborative approaches. Research methodologies such as qualitative research and empirical approaches were evident. Top-cited publications demonstrated enduring impact, while institutions and countries represented the multidimensional nature and global relevance of this field. The outcomes of this bibliometric analysis suggest that community-institutional partnerships, cooperative behavior, interprofessional relations, and government are the most important aspects of social partnerships embracing education entities. The results also imply that qualitative research is a valuable approach for investigating academic-practice collaborations. The findings of this study can inform policymakers about the need to consider strategies that promote interdisciplinary collaboration and address the evolving healthcare landscape.